Migrating Cyclists and Identity Reconstructions: Two Tales of Living and Parting the Dream - Diakaki, Ελένη; Chroni, Στυλιανή «Ανή»; Goudas, Μάριος (Inquiries in Physical Education and Sport, 2016)
The present study delves into two cases of sport labor migration and athlete identity, as we learn from two migrating athletes about the narrative mechanisms used to reconstruct their priorities and identities. Low-structured interviews were conducted with elite level male cyclists who migrated from Greece upon signing professional contracts with European continental teams. To immerse into the experiences, we employed the dialogic/performance analysis and, along with the theoretical framework of identity narratives (Douglas & Carless, 2006), this helped us co-construct a relational and a discovery tale. The narrations reveal that the cyclists‟ physical and mental relocations triggered and intensified processes of identity negotiation, formation, and reconstruction. These processes are traced in the narrative schemata they used as they tried to attain or maintain integrity, along with a sense of coherence between the lived and the told. A continuous negotiation took place between the self, the society, and the sport culture, as they struggled to find their fit within the stereotypically-accepted sport success stories. The findings are discussed with regard to migrant cyclists‟ psychology, identity development, and well-being, while highlighting the need to enrich the narrative repertoire in the elite sport culture, as it can promote and safeguard athlete identity and well-being.